Addressing inefficient post-harvest practices to mitigate food waste in Malaysian food services - Shahidah Md Nor; Nur Zulaily Zulfahrin; Mohamad Syahrul Nizam Ibrahim (University of Bonn, 2025)
In Malaysia, the small food producers include restaurant owners and hawkers. Studies have conclusively shown that food services contribute to approximately 26% of national food waste, primarily driven by inefficient post-harvest handling practices. In this study, the cause of inefficient post-harvest handling was identified with the aim of improving the management of fresh-cut produce within the food service industry. A total of 50 participants comprising cooks, kitchen staff, and restaurant managers were engaged to provide a comprehensive assessment of fresh-cut vegetable handling practices. This focus is particularly pertinent given that fresh vegetables are integral to Malaysian cuisine, and their improper handling can significantly contribute to food waste. The survey covers washing practices, storage methods, packaging type and food safety measures implemented throughout the handling of fresh vegetables until they are transformed into cooked products. The studies revealed several key findings, highlighting that inadequate temperature control and inconsistencies in cold chain logistics led to visible damage, wilting, and microbial contamination, especially in highly perishable vegetables like broccoli and salad. The predominant preservation methods identified were the removal of spoiled portions and size-based sorting. Nevertheless, limited adoption of refrigeration and advanced preservation technologies were the major causes of food waste and spoilage among the food handlers who are involved in food service industry. The finding obtain from this study is crucial to be used as fundamental background to set up the standardized protocol among small food handlers in Malaysia.